Halal Friendly Tourism Policy In Banyuwangi - Jauhariyah, Nur Anim (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This study discusses halal tourism which is one of the policies of the Banyuwangi Regency Government in the effort of developing tourism to increase tourist visits in Banyuwangi Regency. The objectives in this study are 1) Knowing the percentage of tourist visits in Banyuwangi Regency; 2) Knowing the strategies of the local government in developing halal friendly tourism in Banyuwangi. This research uses a quantitative approach with secondary data support. The results showed that 1) The number of tourists both archipelago and foreign tourists in Banyuwangi Regency has increased every year. The highest growth of tourist arrivals from the archipelago was in 2016 at 52.11% and the lowest in 2018 was 2.16%, while the highest foreign tourist arrivals were in 2016 at 40.09% and the lowest in 2018 at 0.23%; 2) The policy strategy in developing halal tourism in Banyuwangi Regency is based on market segments not only limiting visitors who specialize in women`s areas but rather emphasizing the need for innovations that can hit market segments. So that visitor interest in the concept offered can increase the number of tourists coming to tourist destinations in Banyuwangi. Keywords: Halal Tourism, Number of visits, Banyuwangi